The Collection and Application of Autologous Amniotic Fluid to Cesarean Delivery Closure - Grotegut, Chad A.; Weaver, Kristin E.; Fried, Lena; Dotters-Katz, Sarah K.; Gilner, Jennifer B. (American Journal of Perinatology Reports, 2024)
Background Amniotic fluid and amnion membranes have been used in surgery specialties to improve wound healing and decrease surgical adhesion formation.Objective The objective was to determine if amniotic fluid could be collected at cesarean delivery and then reapplied to the layers of the closure using the CeaLogic Specimen Collection and Ratio Applicator Kit.Study Design Twenty pregnant individuals who met inclusion and exclusion criteria were enrolled. Amniotic fluid was collected at artificial rupture of the membranes using the collection kit. Autologous amniotic fluid was then transferred to the applicator kit, mixed with calcium chloride solution, and applied directly to each of the surgical repair layers during closure: closed hysterotomy incision, closed fascial incision, closed subcutaneous layer (if applicable), and closed skin. Subjects were then followed for six weeks. Photographs of the incision were taken immediately following surgery, one-week following surgery, and at the four-week postpartum visit. The Modified Hollander Cosmesis Score was used to assess wound appearance.Results Twenty pregnant individuals who met inclusion and exclusion criteria were enrolled and all completed the study. The mean volume of amniotic fluid collected was 30 ± 19 mL. The median (IQR) Modified Hollander Cosmesis Score (Range 0-best, to 6-worst) at the one week and four-week postpartum visits was 0 (0,1) and 0 (0,2), respectively. There were no wound complications nor surgical site infections among the cohort. Further, there were no unscheduled visits for wound issues among any of the subjects.Conclusion The CeaLogic Specimen Collection and Ratio Applicator Kits can be used to collect and reapply autologous amniotic fluid at the time of cesarean delivery. Future studies are needed to determine if the application of autologous amniotic fluid to cesarean delivery closure can improve cosmesis and wound healing, as well as decrease the risk for the development of intraabdominal adhesions.
Keywords: allograft; amniotic fluid; autologous; cesarean delivery; postsurgical adhesions; scar tissue; surgical site infection; wound complications; wound cosmesis; wound infection